Strategies to improve the immunogenicity of prM+E dengue virus type-2 DNA vaccine - Chutitorn Ketloy (2018)
© 2017, Allergy and Immunology Society of Thailand. All rights reserved. Background: An important goal for dengue vaccines is to induce a high and durable level of neutralizing antibody. Objective: Three strategies were investigated for improving the immunogenicity of a prM+E dengue serotype 2 (DENV-2) DNA vaccine: 1) expression in two different plasmids; 2) adjustment of dose; and, 3) introduction of the E sequence of Japanese encephalitis virus (JEV) at the carboxy-terminal portion of DENV-2 E. Methods: Expression cassettes were designed to encode a full-length prM+E sequence of DENV-2 virus employing human-preferred codons (D2prMEopt), or a chimeric prM+E sequence in which the 100-residue carboxy-terminal region of E was derived from JEV (D2prMEJE20opt). pHIS and pCMVkan in the presence and absence of CpG motif, respectively, were used for cassette expression. The immunogenicity was compared in mice. Results: Three injections of full-length-D2prMEoptin pHIS and pCMVkan induced a comparable neutralizing antibody titer at post-week-2-injection and post-week-4-injection. The 100-μg DNA dose induced a numerically but not statistically higher neutralizing antibody titer than the 10-µg dose. The chimeric-D2prMEJE20optproduced higher extracellular prM and E protein levels in transfected Vero cells, but had a tendency to induce a lower neutralizing antibody titer in mice when compared with the full-length-D2prMEopt. To optimize the immunogenicity of D2prMEopt-DNA candidate, both expression plasmids can be used to generate reproducible high neutralizing titer. A higher dose of DNA immunogen may induce a higher neutralizing antibody response. Conclusion: The strategy of the C-terminal region chimeric counterpart with JE20 did not improve but may have reduced the induction of neutralizing antibodies.